PENERAPAN TEORI KONSTRUKTIVISME MENURUT JEAN PIAGET DAN TEORI NEUROSCIENCE DALAM PENDIDIKAN / APPLICATION OF CONSTRUCTIVISM THEORY ACCORDING TO JEAN PIAGET AND NEUROSCIENCE THEORY IN EDUCATION - Ulya, Zihniatul (Al-Mudarris: Journal Of Education, 2024)
This study examines the application of constructivism theory according to Jean Piaget and neuroscience theory in education. The aim of this research is based on several descriptions of constructivism theory according to Jean Piaget and neuroscience theory in education. It is hoped that it will be able to understand how students learn and its application and how students' brains work so that they can learn according to their talents and interests so that learning becomes fun. The research method used is qualitative research using library research to obtain data from various sources, namely books, journals, articles and several other scientific works related to this topic. Then from these sources, they are studied, analyzed and described, giving rise to four discussions, namely the concept of constructivism theory, neuroscience theory, the application of constructivism and neuroscience in education, and the theory of constructivism and neuroscience in education according to Muslim scientists. The results of this research are constructivism theory in learning, namely that teachers are not the only source of learning, while neuroscience theory supports students in achieving what students want according to their brain abilities. The learning process takes into account the natural working processes of the student's brain. Muslim scientists who developed learning theories similar to constructivism theory were Ibnu Khaldun, Ki Hajar Dewantara, and other scientists, while Muslim scientists who had discussions similar to neuroscience were Imam Ghazali, Ibnu Sina and Al-Farabi.